Description of five new Pantecphylus species from Kivu, the East Province of Democratic Republic Congo (Ensifera: Tettigonioidea: Pseudophyllidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Before the present studies were undertaken, two species of the genus Pantecphylus Karsch, 1891 were described, the genus type, P. cerambycinus Karsch, 1891, and P. major Griffini, 1909, the latter much bigger and more spiny than the former. P. cerambycinus is known from Cameroon and P. major was collected near the Congo delta. Recently, a second species, P. kamerunus Schmidt, 2003, was described from Cameroon. Examining the material of 12 specimens (5 males and 7 females) sampled in the Kivu Province (Democratic Republic Congo), mainly preserved in the African Museum Tervuren and the Natural History Museum of London, five further species were described. According to the sites of collection, the species were named P. kivuensis, P. irangii, P. meshei, P. manyemai, and P. helleri; the latter was dedicated to the collector. In most cases, the holotype was the only known one. Most of females could not surely be attached to one of the species described. For the separation of the species, the external male genitalia were most useful, besides the shape and width of the fastigium verticis. For the identification of females, their collection sites were helpful. However, no female was chosen, and should be used as species type, as happened for P. cerambycinus. For males, a key was presented. The unusual structures of the hind wings of both sexes may be important for further differentiation of the species, specially in females, regarding stridulation and communication.
Keywords: Pantecphylus; Pseudophyllidae; Kivu Province; Central Africa; Democratic Republic Congo